2007
DOI: 10.1086/521397
|View full text |Cite
|
Sign up to set email alerts
|

Global Properties of the Globular Cluster Systems of Four Spiral Galaxies

Abstract: We present results from a wide-field imaging study of the globular cluster (GC) systems of a sample of edge-on, SbSc spiral galaxies $7-20 Mpc away. This study is part of a larger survey of the ensemble properties of the GC populations of giant galaxies. We imaged the galaxies in BVR filters with large-format CCD detectors on the WIYN 3.5 m telescope to projected radii of $20-40 kpc. For four galaxies (NGC 2683, NGC 3556, NGC 4157, and NGC 7331), we quantify the radial distributions of the GC systems and estim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 42 publications
3
74
1
1
Order By: Relevance
“…Because any intermediate merger products are created from identical building blocks as described in assumption 1, the number of GCs simply scales linearly with assembled galaxy mass, regardless of the details of the merger tree. This offers a natural explanation for the empirical result that all but the latest type spirals (see § 5) show a constant specific frequency of GCs: the observed Tvalue (Zepf & Ashman 1993) is ∼2 GCs per 10 9 M , (Goudfrooij et al 2003;Rhode et al 2007). This value is likely a lower limit because (i) not all GCs will survive and (ii) the faintest GCs might be missed in surveys.…”
Section: No 2 2008 Are Globular Clusters Remnant Nuclei? L113mentioning
confidence: 88%
“…Because any intermediate merger products are created from identical building blocks as described in assumption 1, the number of GCs simply scales linearly with assembled galaxy mass, regardless of the details of the merger tree. This offers a natural explanation for the empirical result that all but the latest type spirals (see § 5) show a constant specific frequency of GCs: the observed Tvalue (Zepf & Ashman 1993) is ∼2 GCs per 10 9 M , (Goudfrooij et al 2003;Rhode et al 2007). This value is likely a lower limit because (i) not all GCs will survive and (ii) the faintest GCs might be missed in surveys.…”
Section: No 2 2008 Are Globular Clusters Remnant Nuclei? L113mentioning
confidence: 88%
“…This constant density background is assumed to be due to contaminants in the photometric object list. This approach has been taken by Rhode et al (2007Rhode et al ( , 2010 and Kartha et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…THP acknowledges support in form of the Plaskett Research Fellowship at the Herzberg Institute of Astrophysics of the National Research Council of Canada Chandar et al (2004). The dotted lines show the range of values seen for the total S N in late-type spirals (Goudfrooij et al 2003) while the dashed line depicts a least-square fit to the S N of blue clusters (Rhode et al 2007). Right: The number of red clusters as a function of the bulge V luminosity.…”
Section: Discussionmentioning
confidence: 99%
“…For our sample galaxies, values for both the total S N and the blue S N are shown. Total S N values for early-type and late-type spirals from Goudfrooij et al (2003), Rhode et al (2007), and Chandar et al (2004) are also shown. We see that our blue S N values (0.34 -0.84) mostly lie within the typical S N values for late-type spirals (0.55±0.25) found by these authors.…”
Section: Specific Frequency Of Globular Clustersmentioning
confidence: 99%